USE OF INNOVATIVE TECHNOLOGIES IN EDUCATIONAL PROCESSES AND IMPROVEMENT OF DESIGN - Shermukhamedov R. S. (European Science Publishing, 2024)
This article shows interactive methods, application and design methods of innovative technologies in technological education classes.
Keywords: interactive methods, innovative technologies, project, drawing, equipment, square.